Fundamentals of calculus / Shamsatun Nahar Ahmad, Farah Suraya Md Nasrudin and Muhammad Yassar Yusri - Ahmad, Shamsatun Nahar; Md Nasrudin, Farah Suraya; Yusri, Muhammad Yassar
Fundamental of Calculus contains five chapters emphasising fundamental concepts from calculus and the application of these concepts to selected problems. Chapter One is a review of j evaluation of functions and introduces the concepts of limits and continuity of the functions. Chapter Two introduces the differential calculus and develops differentiation formulas and rules for finding the derivatives associated with a variety of basic functions. Chapter Three investigates selected applications of the differential calculus. Chapter Four introduces the integral calculus and develops indefinite and definite integrals. Rules for integration and the construction of integral are demonstrated throughout the chapter with many examples. Chapter Five investigates selected applications of integral calculus in particular area between two curves and volume of the solid.